2017
DOI: 10.17770/etr2017vol2.2523
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Student’s E-Portfolio

Abstract: Student-oriented approach in education has received a comprehensive description in numerous works of Russian and foreign researchers and continues to evolve rapidly. The implementation of student-oriented approach, the information and methodological support of students throughout the training period are the most effective when used of electronic information-educational environment of high school. The purpose of this article is to analyze the possibilities of using electronic information-educational university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Other environmental factors that influence KMS adoption are cloud computing and big data analytics, as mentioned and illustrated by Mohamad et al [98], Medvedeva et al [99], and Dening et al [100]. Prior studies also indicated that the used software and hardware when implementing KMS are among the factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Other environmental factors that influence KMS adoption are cloud computing and big data analytics, as mentioned and illustrated by Mohamad et al [98], Medvedeva et al [99], and Dening et al [100]. Prior studies also indicated that the used software and hardware when implementing KMS are among the factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Another environmental factor that influence e-portfolio adoption is the cloud as mentioned and illustrated by Mohamad, Embi [100], Medvedeva, Martynyuk [101], and Dening, Holmes [87]. Prior studies also indicted the used software and hardware when implementing e-portfolio as among the factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In the Internet era, e-Portfolio evaluation can truthfully assess the education and teaching process through information technology. This technique has broad application prospects, by virtue of several advantages: diverse evaluation subjects, emphasis on process evaluation, support to individualized development, and integration between teaching and evaluation [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%